THE JOURNAL OF THE COURT SESSION AS A SOURCE OF INFORMATION ON THE LEGALITY OF THE DECISIONS OF THE INVESTIGATING JUDGE REGARDING THE GRANT OF PERMISSION TO CONDUCT UNDERCOVER INVESTIGATIVE (SEARCH) ACTIONS - Tarasiuk, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to investigate the existence of exceptions in the criminal procedural legislation regarding the obligation to keep a journal of the court session during the consideration of requests for permission to conduct undercover (search) investigative actions (UI(S)A) by investigative judges. To study the influence and weight of the information of the journal of court sessions on the assessment of the legality of the decisions of investigating judges on granting permission to conduct UI(S)A in particular in the context of the application of the «fruits of the poisonous tree» doctrine to the evidence obtained as a result of conducting UI(S)A based on the decisions of the investigating judge on the granting of permission for the conduct of UI(S)A, which were decreed in court sessions without keeping a journal of the court session. Methods of research: general scientific and special legal methods, in particular the method of analysis, the system-functional method and the formal-legal method. Results: conclusions were formed about the significance of the impact of recording the court session for consideration of petitions for granting permission to hold UI(S)A in the journal of court sessions on the effectiveness of the exercise of the right to defense and, in particular, on the procedural right to submit substantiated objections to the rulings of the investigating judge during the preparatory hearing. Discussion: the criminal procedural legislation, which is drawn up in accordance with the Constitution and the Criminal Procedure Code and other legal acts, contains the right of the defense party to appeal the decisions of the investigating judges and, in some cases, to file objections to the rulings of the investigating judges during the preparatory hearing. The realization of these rights is complicated by a specific approach to the consideration of requests for permission to conduct UI(S)A and, accordingly, the issuing of resolutions on granting such permission. The specificity is that during the trial, the state secrets legislation must be observed, which is special in this case and may establish certain limitations and rules of the trial. Court practice shows abuse of the norms of the Criminal Procedure Code by investigating judges, which in turn calls into question the legality of such decisions. The second factor, which also calls into question the validity of such decisions, is a derivative of the first and consists in the impossibility of the defense party exercising the right to question the validity of the decision of the investigating judge to grant permission for the conduct of the UI(S)A due to the lack of a procedural source of information about the progress of the trial - the journal of the court session, namely, the presence during the consideration of the petition of the person who submitted such a petition (investigator or prosecutor) and that person’s evidence to the investigating judge. Such evidence is the basis for making a reasoned decision, and the absence of requirements in the legislation makes it impossible to establish whether any evidence was submitted at all.